New Generation Solar Cooling and Heating Systems with IEA SHC Task 53: Overview and First Results. (May 2015) - Mugnier, Daniel; Fedrizzi, Roberto; Thygesen, Richard; Selke, Tim
Abstract: Solar cooling technology is currently facing a very exciting challenge. Air conditioning is a large and growing energy consumer, especially in sunny and developing countries. Worldwide efforts to develop renewable energy solutions must address this critical cooling application. A new Generation of Solar Cooling systems including the coupling between Photovoltaic modules and a reversible heat pump is very promising and able to represent a cost competitive solution both reliable and efficient. To address this new generation of solar cooling, a new IEA Solar Heating and Cooling Program Task, called Task 53 has just started for 3.5 years and will be described. This paper will first concentrate on the description of Task 53 with its objectives and work plan then it will show the first results such as the state of the art of the new generation solar cooling systems. Then, a virtual case study on the cost competitiveness of a PV reversible heat pump installed in Madrid for cooling and heating will be presented, underlining that such a solution already would present a payback time of less than 10 years in the Spanish economical today's conditions